Agroforestry in the UK - Burgess, Paul J. (The Royal Forestry Society, 2017)
The Royal Forestry Society, the Woodland Trust and the Soil Association are hosting a one-day conference on ‘Agroforestry: Improving Productivity for Farmers and Foresters’ at Cranfield University, Bedfordshire on 22 June 2017. This will be followed by a one-day Farm Woodland Forum workshop, including a field visit to the apple and cereal agroforestry system of Stephen Briggs. To set these events in context, this article explains why UK agroforestry is important, topical, how it is being used to market food products, improve productivity, address climate-change and flood management, and how it depends on dynamic farmers and foresters.